Analisis Penerapan Konsep Mewirausahakan Birokrasi Terhadap Sistem Pelayanan Rakyat Sidoarjo (SIPRAJA) Sebagai Jawaban Tuntutan Pelayanan Publik yang Dibutuhkan oleh Masyarakat - Arna Dea Septiananda; Muhtar Haboddin; Angga Sukmara C. Permadi (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
The Sidoarjo Public Service System (SIPRAJA) is one of the innovations in public service digitalization initiated by bureaucrats at the Sidoarjo Regency Secretariat. This study aims to determine the process of creating the Sipraja innovation; assess the relevance of applying the Reinventing Government concept; determine Sipraja’s ability to respond to public service demands in Sidoarjo; and evaluate and identify gaps in Sipraja from the innovation process to implementation. This study uses a qualitative, case-study approach. This research was analyzed using five principles from the concept of reinventing government: competitive government, mission-driven government, anticipatory government, entrepreneurial government, and decentralized government. The results of this study indicate that the concept of reinventing government is relevant to Sipraja. The application of the principles in this concept also contributes to the analysis and identification of various challenges and obstacles in Sipraja. Sipraja has great potential to meet the public service demands of the people of Sidoarjo. Basically, Sipraja is a brilliant innovation idea, but it lacks the commitment and efforts of stakeholders to ensure the excellence of Sipraja’s service performance until the implementation stage. This is an important note that needs to be addressed immediately to support the creation of efficient and effective digital public services that people in Sidoarjo can rely on.